UNIQUE WORLD OF THE CREATOR - Kaztuganova, A.Zh.; Omarova, A.K.; Karomat, D.F. (Scientific Journal of Pedagogy and Economics, 2020)
The article describes some issues of formation of personal qualities and spheres of activities of N.Tlendiev, that have been determined through ethnicity hearing. The range of issues include the analysis of performing and composing activities, stage behavior, as well as innovative performance style, introduced by the famous kuishi into Kazakh music. On the one hand, the formation of N. Tlendiev as a person was determined by the strength of ethnic ear, and, on the other, by the depth of professional knowledge. It was determined that in all his diverse creative activities, that is, performing, composing, conducting or organizing activity, the gift of ethnic ear and high professional competence played an important role. The rich images reflected in his musical compositions, a wide range of thematic lines, the variety of musical methods and instrumental techniques that have not been studied, will result in new research works in the future. In the future the vital activities of N. Tlendiev should be investigated from a scientific point of view, confirmed by documents and facts, and the particular monographic work should be devoted to them.